2005
DOI: 10.1128/aem.71.5.2433-2437.2005
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Diploscapter sp. Strain LKC25, a Bacterivorous Nematode from Soil, as a Vector of Food-Borne Pathogenic Bacteria to Preharvest Fruits and Vegetables

Abstract: Diploscapter, a thermotolerant, free-living soil bacterial-feeding nematode commonly found in compost, sewage, and agricultural soil in the United States, was studied to determine its potential role as a vehicle of Salmonella enterica serotype Poona, enterohemorrhagic Escherichia coli O157:H7, and Listeria monocytogenes in contaminating preharvest fruits and vegetables. The ability of Diploscapter sp. strain LKC25 to survive on agar media, in cow manure, and in composted turkey manure and to be attracted to, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…Their ability to act as vectors and shed pathogenic bacteria in anthropogenic or arable soils has caused some concern for food production and public health (Gibbs et al. 2005; Locas et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to act as vectors and shed pathogenic bacteria in anthropogenic or arable soils has caused some concern for food production and public health (Gibbs et al. 2005; Locas et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This study proved the concept that free-living worms can serve as a source of bacterial pathogens in melons and other produce growing on the ground. In a more recent study, Gibbs et al (2005) demonstrated the ability of Diploscapter sp., another free-living nematode commonly found in the rhizosphere of crop soils, to survive in manure, ingest S. Poona and other pathogens, and then to shed these pathogens 24 h after exposure to the inoculated manure. These studies indicate that the primary point of contamination of melons may be the field via environmental vectors.…”
Section: Preharvestmentioning
confidence: 97%
“…An exhaustive list of known pathogens of Caenorhabditis elegans, including various opportunistic and true human pathogens, is found in Sifri et al (2005). Caenorhabditis elegans, used as a model host in agriculture studies, and the nematode Diploscapter sp., commonly found in agricultural soil and in compost, can vector various strains of E. coli O157:H7, Salmonella sp., and Listeria monocytogenes , as those nematodes are attracted to the pathogenic bacteria and are able to ingest and transport them in their digestive tract (Gibbs et al 2005). Caenorhabditis elegans has also been shown to transmit bacteriophages from one bacterial colony to another on a Petri dish (Dennehy et al 2006).…”
Section: Survival Of Microorganisms Inside Nematodesmentioning
confidence: 99%
“…The viability of the pathogenic microorganisms that have been ingested without being digested or biodegraded by their predators can be maintained (Barker and Brown 1994). This resistance to digestion has been reported numerous times in amoebae (Barker and Brown 1994;Winiecka-Krusnell and Linder 1999;Greub and Raoult 2004) and nematodes (Chang et al 1960a;Caldwell et al 2003;Gibbs et al 2005) but has not been reported for most zooplankton organisms (rotifers, copepods and cladocerans), even though the study of their predation and grazing activities under diverse conditions has been widely documented.…”
Section: Introduction and Objectivesmentioning
confidence: 95%